THE EFFECT OF TRAINING METHOD AND LEG POWER TOWARD DOLYO CHAGI ABILITY (An experimental study on Taekwondo Athletes of Lampung Province) - Asmawi, Moch.; Wiguna, Ida Bagus (Program Pascasarjana Universitas Negeri Jakarta, 2015)
The objective of this research is to investigate the effect of training method and leg power toward dolyo chagi ability of taekwondo athletes.In this research factorial design 2 x 3 was applied. The sample of this research is 60 athletes and was chosen by purposive sampling technique. From the result of data analysis and interpretation,it can be concluded that : (1) There is difference influence between the plyometric training, saq and circuit toward dolyo chagi ability (2) There is difference influence between the strong leg power group and weak leg power group toward dolyo chagi ability (3) There was an interaction between training method and leg power toward dolyo chagi ability. (4) On strong leg power group, the ability of dolyo chagi with plyometric training method was better than saq training. (5) On strong leg power group, the ability of dolyo chagi with plyometric was better than circuit training. (6) On strong leg power group, the ability of dolyo chagi with saq training method was better than circuit training. (7) On weak leg power group, the ability of dolyo chagi with saq method was better than plyometric method. (8) On weak leg power group, the ability of dolyo chagi with circuit method was better than plyometric method